Asean Bond Market Development : Where Does it Stand? Where is it Going? - Pradhan, Mahmood (IMF Working Papers; Working Paper ;, 2011)
Since the Asian crisis, ASEAN5 countries have expended considerable effort in trying to develop their domestic bond markets. Yet today these markets are not much larger, relative to GDP, than they were a decade before. How can we explain this? And does this mean that domestic markets have not, in fact, developed? The paper argues that bond market growth has been held back by a sharp fall in investment rates, which has left firms with little need for bond borrowing. Even so, markets have developed in other ways, to such an extent that substantial amounts of foreign portfolio investment have begun to flow into ASEAN5 bonds. These developments have important ramifications. With the investor base growing and infrastructure investment likely to rise, ASEAN5 bond markets could expand rapidly over the next decade, holding out the prospect that the region could finally achieve "twin engine" financial systems.